Geospace Plume and Its Impact on Dayside Magnetopause Reconnection Rate. Issue 6 (21st June 2021) - Zou, Ying; Walsh, Brian M.; Shi, Xueling; Lyons, Larry; Liu, Jiang; Angelopoulos, Vassilis; Ruohoniemi, John M.; Coster, Anthea J.; Henderson, Michael G.
Abstract: The role a geospace plume in influencing the efficiency of magnetopause reconnection is an open question with two contrasting theories being debated. A local‐control theory suggests that a plume decreases both local and global reconnection rates, whereas a global‐control theory argues that the global reconnection rate is controlled by the solar wind rather than local physics. Observationally, limited numbers of point measurements from spacecraft cannot reveal whether a local change affects the global reconnection. A distributed observatory is hence needed to assess the validity of the two theories. We use THEMIS and Los Alamos National Laboratory spacecraft to identify the occurrence of a geospace plume and its contact with the magnetopause. Global evolution and morphology of the plume is traced using GPS measurements. SuperDARN is then used to monitor the distribution and the strength of dayside reconnection. Two storm‐time geospace plume events are examined and show that as the plume contacts the magnetopause, the efficiency of reconnection decreases at the contact longitude. The amount of local decrease is 81% and 68% for the two events, and both values are consistent with the mass loading effect of the plume if the plume's atomic mass is ∼4 amu. Reconnection in the surrounding is enhanced, and when the solar wind driving is stable, little variation is seen in the cross polar cap potential. This study illuminates a pathway to resolve the role of cold dense plasma on solar wind‐magnetosphere coupling, and the observations suggest that plumes redistribute magnetopause reconnection activity without changing the global strength substantially. Plain Language Summary: A variety of magnetospheric plasma populations exist at the interface where the solar wind encounters the magnetosphere, and they can impact the efficiency of the energy transfer from the solar wind to the magnetosphere. One population of particular interest is geospace plumes, which are plumes of cold dense plasma of ionospheric origin drifting sunward toward the magnetopause during enhanced geomagnetic activity. Plumes often have a density much higher than the other magnetospheric populations and can therefore mass load the dayside magnetopause slowing down magnetic reconnection. However, whether reconnection is slowed at a local or global scale is under debate. Observationally, point measurements from spacecraft cannot reveal whether a local change affects the global reconnection and a distributed observatory is hence needed. In this study we strategically coordinate measurements made by THEMIS and Los Alamos National Laboratory spacecraft, GPS network, and SuperDARN to investigate the effect of plumes on reconnection. Our results suggest that plumes decrease the local reconnection rate at the plume longitude and increase the reconnection rate in regions adjacent to the plume. When the solar wind is stable, the global reconnection remains unchanged. Such observations illuminate a pathway to resolve the role of cold dense plasma on solar wind‐magnetosphere coupling. Key Points: We strategically coordinate measurements made by THEMIS and Los Alamos National Laboratory spacecraft, GPS network, and SuperDARN to investigate geospace plumes Plumes decrease the local reconnection rate at the plume longitude and increase the reconnection rate in regions adjacent to the plume When the solar wind is stable, the global reconnection remains unchanged in presence of plumes, supporting a global‐control theory